Research Progress on Chemically Modified Plant Polysaccharides: Bioactivities and Applications in the Food Industry - Na ZHANG; Yang LIU; Xiaoqiang CHEN; Miaomiao YING (Shipin gongye ke-ji)
Plant polysaccharides represent a class of naturally occurring macromolecular polymers that exhibit diverse bioactivities, including antioxidant, hypoglycemic, immunomodulatory, antitumor, and antibacterial. A burgeoning body of research suggests that polysaccharide bioactivities can be enhanced via structural modifications. This study presents five chemical modification methods for polysaccharides—sulfation, phosphorylation, acetylation, carboxymethylation, and selenization—with particular emphasis on their effects on polysaccharide bioactivities. Furthermore, it summarizes the applications of chemically modified polysaccharides as food additives, edible packaging materials, functional food components, carriers, and food ingredients. This information provides a theoretical framework to fully investigate the bioactivities of plant polysaccharides and advance their product development and research in the food industry.